(untitled) (Open Academia: Journal of Scholarly Research, 2023)
The problem of objectivity in assessing the efficiency of waterflooding of an oil field at all stages of development is an urgent task. Ways to solve the problem may be different. The first method is the use of geological models of productive formations that are sufficiently adequate to real conditions and complex hydrodynamic models that describe the mechanism of the filtration process of formation and working fluids injected into the formation